Refugee women’s health: needs, knowledge, and behaviors of female refugees - Wiens, Jessica; Gallagher, John; Lyden, Elizabeth; Cartwright, Sara; Dougherty, Collin; Toure, Drissa; Maxwell, Jessica (Global surgical education : journal of the Association for Surgical Education, 2023)
Background Refugees entering the USA undergo initial health screening. However, little guidance on preventative medicine is provided. We examined health knowledge and attitudes towards recommended screening protocols for breast and cervical cancer. Methods Surveys developed by a panel of experts and were administered to adult female refugees via convenience sampling. Count and percentages were used to summarize data. Chi-squared tests were used. Tests were two-sided and p value. Results Most respondents identified as Burmese. Previously living in urban settings was associated with increased awareness of breast cancer ( p = 0.043), cervical cancer ( p = 0.034), as well as knowledge about Pap smear ( p = 0.01)), and HPV vaccine ( p = 0.0145). Similarly, longer time in a refugee camp was associated with less knowledge of breast cancer ( p = 0.034). Women with greater than high school education and household incomes greater than $25,000/year exhibited more health knowledge than those with less education and lower incomes. Conclusion Previously living in an urban setting was associated with increased awareness of breast and cervical cancers. Subjects with greater than high school education and current household incomes of greater than$25,000 were more likely to have knowledge on breast and cervical cancers. This study represents an early step in understanding health knowledge gaps in the female refugee population. This data may be used to inform future outreach and education programs in a culturally sensitive manner.